Phase I/II clinical trial on the safety and preliminary efficacy of donor-derived anti-leukemia cytotoxic T lymphocytes for the prevention of leukemia relapse in children given haploidentical hematopoietic stem cell transplantation: study rational and design - Montagna, Daniela; Comoli, Patrizia; Tanzi, Matteo; Montini, Enrica; Moretta, Antonia; Taurino, Gloria; Boghen, Stella; Panigari, Arianna; Mina, Tommaso; Giorgiani, Giovanna; Del Fante, Claudia; Perotti, Cesare; et al. (Frontiers in Immunology, 2025)
Leuk-CTL-001 (EudraCT n. 2019-003362-41) is a Phase I/II clinical trial on the safety and preliminary efficacy of donor-derived anti-leukemia cytotoxic T lymphocytes (CTLs) for the prevention of leukemia relapse in children given haploidentical hematopoietic stem cell transplantation (HCT). The prognosis for children affected by acute leukemia and transplanted in an advanced disease stage, in the presence of measurable minimal residual disease (MRD) or with unfavorable cytogenetic abnormalities, is still poor and often less than 50%. Adoptive cell therapy based on the infusion of donor-derived CTLs able to recognize patients’ leukemia blasts (LB) is a promising approach to control leukemia relapse after allogeneic HCT. We previously described a procedure for ex vivo generating and expanding large numbers of donor-derived anti-leukemia CTL in compliance with Good Manufacturing Practice (GMP). The analysis of all batches of anti-leukemia CTLs produced so far documented that the majority of effector cells were CD3+/CD8+ cells, with a memory/terminal activated phenotype displaying efficient capacity to lyse patients’ LB and to secrete IFNγ and TNFα in response to leukemia cells. The Leuk-001 trial explores the safety of infusion of escalating doses of anti-leukemia CTLs in a cohort of high-risk relapse pediatric patients given haploidentical HCT for acute leukemia, starting within 60 days after transplantation. The safety is evaluated in terms of incidence of acute and chronic graft versus host disease (GVHD). The secondary objective is the evaluation of efficacy defined as cumulative incidence of relapse.Clinical Trial Registrationhttps://www.isrctn.com/, identifier ISRCTN13301166; https://clinicaltrials.gov/, NCT06865352.